Implikasi Hukum Penggunaan Media Sosial Sebagai Sarana Pers - Rain Victoria Lumban Batu; Maura Viranti A.Syira Adam; Riehza Faizal Ramdhani; Achmad Juneadi; Taun Taun (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of social media as a means of the press has various legal implications amidst the rapid development of information technology. Social media makes it easy to disseminate information quickly and widely, but on the other hand, the absence of clear regulations in categorizing it as part of the formal press raises legal problems, especially related to responsibility for content, protection of individual rights, and freedom of expression. This study aims to examine the position of social media in the legal framework of the press in Indonesia, and to analyze its legal consequences for users who act as conveyors of public information. Using the normative juridical method, it was found that social media has not received explicit recognition as a press entity in the Press Law, thus creating legal loopholes in terms of accountability and legal protection. Regulatory updates are needed to ensure legal certainty and maintain a balance between freedom of expression and legal responsibility in the digital era.